Rivalitas Iran-Saudi-Turki dan Kekhawatiran Ideologis Kaum Wahabi Indonesia terhadap Kesepakatan Nuklir Iran-AS - Chaidar, Al; Sahrasad, Herdi (Universitas Muhammadiyah Yogyakarta, 2017)
The Iran-US agreement on nuclear power has made watershed in Iran-West relations, in which all of nuclear weapons of Iran should be disconnected and frozen so that only the Israelis held a nuclear power in the Middle East.Teheran always says its nuclear activities are for peaceful purposes. Nowadays the international sanctions on Iranian lifted, and Iran is more powerfull to enhance its posture in international arena.This agreement has caused ideological anxiety among the Wahabis with implications that the Wahabis are not happy and they do not like with the strengthening of Iran politically and culturally in globalized world. The Wahabis’ Ideological interests will be erodedto a certain degree with the agreement which would seriously divide the Islamic world by by Sunni-Shia rivalry. However, the rise of Turkey which competed with Iran and Saudi in the political arena of Middle East, would open the Wahabis eyes in Indonesia that maybe Turkey is the hope of the future.